Proteoglycans orchestrate remodeling of prostatic cytoarchitecture after androgenic blockade in old gerbils - Campos, Silvana G. P. [UNESP]; Gonçalves, Bianca F. [UNESP]; Ruiz, Thalles Fernando Rocha; Leonel, Ellen Cristina R.; Ribeiro, Daniele L.; Falleiros Junior, Luiz Roberto; Goes, Rejane M. [UNESP]; Taboga, Sebastião R. [UNESP] (Wiley, 2023)
Background: The aim of this study was to evaluate modifications in proteoglycan morphology and composition in the prostatic stroma of 18-month-old gerbils after surgical castration, in association or not with an androgenic blockade. Methods: The animals (n = 5) were sorted into groups subjected or not to antiandrogen treatment (flutamide 10 mg/kg/day) administered for the total postsurgery period and euthanized at 7- or 30-day postcastration; the control group consisted of intact animals. Tissue analysis included immunohistochemical assessment (perlecan and chondroitin sulfate) and proteoglycan morphology was analyzed by transmission electron microscopy. Results: Chondroitin sulfate frequency was increased 7 days postcastration with an androgenic blockade. The presence of these carbohydrates was rare after 30 days of androgenic blockade treatment. There was a significant increase in the amount of perlecan in the prostate stroma from groups subjected to castration plus flutamide for 7 or 30 days. Ultrastructural analysis showed that the incidence of areas occupied by proteoglycans and basement membrane was altered by treatment. In addition, androgenic blockade results in changes in the amount, thickness, and morphology of these structures. At 30 days postcastration, with or without flutamide treatment, larger proteoglycans were common. Conclusions: In this study, in particular, the decrease in chondroitin sulfate after the longer period might be understood as a prostatic response to androgenic deprivation, while the high frequency and permanence of perlecan led to the assumption that its modulation could be androgen-independent. Length and form alterations in proteoglycans as well as associations among them and with the basement membrane were dynamic events in the prostate microenvironment.
Keywords: castration; chondroitin sulfate; flutamide; perlecan; prostate